IMPLEMENTASI PUTUSAN PENGADILAN HAM DALAM KASUS TRISAKTI: TANTANGAN DAN PELUANG BAGI PENEGAKAN KEADILAN TRANSISI - Fauziyah, Sa’adah (Legal Studies Journal, 2025)
This study examines the implementation of human rights court decisions in the Trisakti case, highlighting significant challenges and opportunities for achieving transitional justice. The Trisakti incident, marked by mass student protests against Suharto's authoritarian regime, involved severe human rights violations, including unlawful shootings and repression of dissent. Despite the legal framework established by Law No. 26/2000 on Human Rights Courts, the implementation of court decisions remains riddled with obstacles, such as legal ambiguities, lack of cooperation from military authorities, and inadequate investigation processes. This study emphasizes the need for a collaborative approach involving the government, civil society, and international organizations to ensure justice for the victims and their families. Furthermore, it underscores the importance of educating law enforcement officials about human rights issues to foster a culture of respect for human rights in Indonesia. Ultimately, this research advocates for collective responsibility among all elements of society to realize transitional justice and uphold the rule of law.